HUBUNGAN TINGKAT PENGETAHUAN TENTANG PENYAKIT DM DENGAN PENGENDALIAN KADAR GLUKOSA DARAH PADA PASIEN DM TIPE II DI RSU PKU MUHAMMADIYAH SURAKARTA - Perdana, Ananda Asriany; Ichsan, Burhannudin; Rosyidah, Devi Usdiana (Biomedika, 2013)
The level of DM knowladge with blood glucose controll was instrument to help diabetic patients did the management of diabetes. Diabetic patients who had more and better informations about DM, than they changed their life style, that could controll their disease. So, they would have longer and better live. This research was observational analytic research with cross sectional approach. The sample was 33 diabetic patients who cared their disease in RSU PKU Muhammadiyah Surakarta and who had ful? lled the predeterminated criteria, it was taking with the purposive sampling technique. The research instrument used the level of DM knowladge quesioner and medical record. From the statistical calculation, it was obtained that P value = 0,042. It could be concluded that there was signi? cant the relationship between the level of DM knowladge with blood glucose controll of type 2 diabetic patients. Pasients who had high level knowladge would have good blood glucose controll.Key Words : Level Knowladge, Diabetes Melitus of Type 2, Blood Glucose